Perkembangan Pendidikan Berkualitas di Indonesia: Analisis SDGs 4 - Riris Lawitta Maulina Siahaan; Juli Arianti; Najdah Thalib (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Sustainable Development Goals (SDGs) are a major topic in the global development agenda discussed by United Nations (UN) member states in Rio De Janeiro, with the aim of replacing the Millennium Development Goals (MDGs). One of the fourteen goals in the SDGs is to ensure equitable and inclusive quality education and increase lifelong learning opportunities for all individuals. This study aims to track the development of education in Indonesia to achieve the SDGs target, namely in building a quality education system and providing fair learning opportunities to all citizens. This study used a descriptive method. The results show that education development indicators in Indonesia continue to show improvement from year to year, thanks to government policies in the education sector, but there are still some challenges that need to be overcome